Networking and Consortia Management Techniques - Malviya, Rama Nand; Kumar, Anil (DESIDOC Journal of Library & Information Technology, 2010)
A single library has limitations of maintaining books/documents/journals and other materials demanded by its client or users. To overcome these types of problems, cooperation among the libraries was initiated and a new concept “Library Consortium” came into existence with a wide coverage. The paper describes the concept of library consortia, networking and consortia management techniques and future of consortia efforts. http://dx.doi.org/10.14429/djlit.27.3.133